IMPLEMENTASI GAME ONLINE TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Nurbiba .; Rosleny B.; Muhlis Madani (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
ONLINE GAME IMPLEMENTATION TOWARDS STUDENTS 'LEARNING MOTIVATION IN PRIMARY SCHOOLSThis study aims to determine the use of online games in students, and to determine the use of online games in motivating students' learning, as well as to determine the positive and negative impacts of using online games on students. This research uses descriptive qualitative. Data was collected through interviews, observation and documentation. This study uses data analysis techniques, which consist of the stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the use of online games in students had disciplinary rules at school, online games were used as a learning resource and means or media, the positive impact of using online games for students could support a fun learning process to facilitate the learning process, while the negative impact of using online games, causing students to become addicted or addicted. So that the decrease in the learning motivation of students. The conclusion of this study is the use of online games is expected to be a source of learning and learning media in the learning process so that students are motivated to learn.